2022
DOI: 10.3390/v14050853
|View full text |Cite
|
Sign up to set email alerts
|

Recent Zoonotic Spillover and Tropism Shift of a Canine Coronavirus Is Associated with Relaxed Selection and Putative Loss of Function in NTD Subdomain of Spike Protein

Abstract: A canine coronavirus (CCoV) has now been reported from two independent human samples from Malaysia (respiratory, collected in 2017–2018; CCoV-HuPn-2018) and Haiti (urine, collected in 2017); these two viruses were nearly genetically identical. In an effort to identify any novel adaptations associated with this apparent shift in tropism we carried out detailed evolutionary analyses of the spike gene of this virus in the context of related Alphacoronavirus 1 species. The spike 0-domain retains homology to CCoV2b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 52 publications
(83 reference statements)
1
14
0
Order By: Relevance
“…2021 ; Vlasova et al. 2021 ; Zehr, Kosakovsky Pond, and Martin 2021 )), transmissible gastroenteritis virus, infecting pigs and feline coronavirus from cats ( Herrewegh et al. 1998 ; Decaro et al.…”
Section: Introductionmentioning
confidence: 99%
“…2021 ; Vlasova et al. 2021 ; Zehr, Kosakovsky Pond, and Martin 2021 )), transmissible gastroenteritis virus, infecting pigs and feline coronavirus from cats ( Herrewegh et al. 1998 ; Decaro et al.…”
Section: Introductionmentioning
confidence: 99%
“…Amino acid sequence alignment of the S1 NTD region (modified from Zehr et al [19]). The blue bar represents the area identified experimentally as being pertinent to sialic acid binding (a viral tropism determinant) in TGEV.…”
Section: Resultsmentioning
confidence: 99%
“…Sequence analysis by Zehr et al [19] identified multiple recombination events between CECoV and FCoV; temporal analysis suggested CCoV-HuPn-2018 may have diverged from a lineage most recently circulating in cats between 1846 and 1976 (95% HPD-Highest Posterior Density Interval), with a median estimate of 1957 [19]. The lack of similarity between 10/22 and CECoV-HuPn-2018 and lack of conserved deletions/unique substitutions between 7/20 and CECoV-HuPn-2018 putatively attributed to loosened sialic acid binding, suggests there is currently unlikely to be a zoonotic threat from these highly prevalent CECoV variants of interest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations